Redefining Evangelicalism from the Margins: South Korean Student Evangelical Experiments, 1986-89 - Seo, Dongjun (Studies in church history, 2025)
Under the 1980s authoritarian regime of Doo-Hwan Chun, a young Christian group emerged from the evangelical majority of Korean Protestantism. On the margins of Korean evangelicalism, this group started to redefine what it meant to be evangelical and to challenge its conservative-leaning socio-political and missiological orientation. This theme of "new evangelicals" or "the evangelical left" has been covered by many scholars in relation to America and Latin America, but not in Asian contexts. This article illuminates the Korean story by analysing the new evangelical experiments of Korean students from 1986 to 1989. It looks at their socio-political and ecclesial background, the tensions between this group and mainstream evangelicalism, and their contribution to the wider Korean evangelical community. Based on in-depth research of Korean primary sources and oral interviews with its key members, this article explores how a new evangelical group at the margins of Korean evangelicalism challenged the centre.